316 IMPACT OF TENNCARE REFORM ON THE CARE OF PATIENTS WITH RHEUMATIC DISEASES. Issue 1 (1st January 2007) - Braverman, A.; Tang, B.; Cross, J.; Raza, S. H.; Nesheiwat, J.; Carbone, L. D.
Abstract : Purpose of Study: To determine the impact of TennCare reform on the care of patients with rheumatic diseases. Methods: The medical records of all patients scheduled to be evaluated in an urban academic rheumatology clinic in the 3 months prior to and in the 3 months following TennCare reform were reviewed to determine differences in show rates. The demographic and disease characteristics, number of active medications, and insurance status of all patients scheduled in the 3 months following TennCare reform was recorded. A telephone survey of patients who did not return to clinic following this reform was done to determine future plans for medical care among those who had been disenrolled from TennCare and the ability to afford medications among those who retained TennCare but who were taking more than five medications. Results: Overall, 402 of the 601 patients scheduled for a rheumatology clinic appointment prior to TennCare reform (67%) showed up for their scheduled rheumatology appointment compared with 362 of 595 patients (61%) scheduled for an appointment following TennCare reform, a difference that was statistically significant ( p = .034). Compared with patients who kept their clinic appointment following TennCare reform (controls), patients who had been scheduled but did not attend their visit (cases) were significantly more likely to have been disenrolled from TennCare ( p < .001). Among cases who had been disenrolled, almost half (45%) did not know where they were going to receive future rheumatic disease care. Among those who retained TennCare, 42% took more than five medications; of these, fewer than half indicated that they could afford to purchase all of their medications. Conclusions: TennCare reform has significantly limited care provided for patients with rheumatic diseases. The long-term consequences of this merit future study.